Exploring the therapeutic impact of Salvia officinalis on lipid and oxidative stress markers in patients with polycystic ovary syndrome – a randomized placebo-controlled clinical trial - Arezoo Maleki-Hajiagha; Faraz Mojab; Fardin Amidi; Leila Amini (BMC Complementary Medicine and Therapies)
Abstract Background Salvia.officinalis (S. officinalis), is recognized for its antihyperlipidemic, metabolism-regulating, and antioxidant properties in diabetic and hyperlipidemic disorders. This study examining its effects on lipid and oxidative stress (OS) markers in patients with Polycystic Ovary Syndrome (PCOS), thereby substantiating its role in managing metabolic disorders. Methods In this randomized placebo-controlled trial was performed in gynecology clinics affiliated to Iran University of Medical Sciences. Accordingly, 70 Iranian married women aged 15–40 years with newly diagnosed PCOS were included. They were randomized to receive either 330 mg of S. officinalis extract or placebo daily for eight weeks. The study outcomes included lipid profile and OS markers. Results The study found a significantly lower triglyceride levels and malondialdehyde after eight weeks of S. officinalis extract intake compared to placebo. Also, the mean change of triglyceride, high-density lipoprotein cholesterol, malondialdehyde, and total antioxidant capacity were statistically significant in intervention group. Conclusion The study demonstrates that S. officinalis extract can significantly reduce triglyceride levels and OS in patients with PCOS, suggesting its potential as an adjunctive natural therapy for managing metabolic and oxidative imbalances associated with this condition. While the extract did not significantly alter other lipid profile markers, the observed improvements highlight the therapeutic promise of S. officinalis. These findings support further investigation into the clinical applications S. officinalis for PCOS and its potential benefits for metabolic health. Trial registration IRCT201504146917N2 on 2015–10-03 (registered while recruiting). Graphical Abstract